Metabolomic fingerprints: seasonal and farm-specific differences in Heterotrigona itama bee bread - Shin, Siong Ng; Nurkhalida Kamal,; Wan, Kiew-Lian; Izfa Riza Hazmi,; Nurul Yuziana Mohd Yusof,; Mohd Faizal Abu Bakar,; Mohd Fahimee Jaapar,; Norela Sulaiman,; Fareed Sairi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Stingless bees’ products such as honey and bee bread are beneficial to human health. However, the metabolite composition within the products may differ according to spatial and temporal factors. This study aims to investigate the impact of spatial and temporal factors on the significant metabolite composition present in Heterotrigona itama bee bread collected from different seasons and types of bee farms. Thus, tandem mass spectrometry (LCMS/MS) based metabolomics analysis was used to achieve the said goal, focusing on H. itama bee bread samples, followed by multivariate analysis using the MetaboAnalyst platform. Our findings revealed significant metabolites that set bee bread samples apart. In terms of temporal factors, the analysis highlights specific metabolites exclusive to the wet season, such as flavones and flavonoids. However, in contrast, during the wet season, there are no significant metabolites in herbal farm samples. The results also underscore the significance of phenolic compounds in wet season samples and as vital metabolites distinguishing the groups. This study highlights a total of 24 annotated significant metabolites identified in different bee bread samples, as well as their capacity to differentiate between seasons and bee farms. Notably, these results suggest a wide variety of potential plant families as a source of bee bread. These findings shed light on the impact of seasons and diverse plant families contributing to bee bread composition, which may impact the growing meliponiculture industry greatly.